GOLD DECORATION OF MONOATOMIC STEPS ON THE 100 SURFACE OF NACL CRYSTALS PRODUCED DURING EVAPORATION IN AIR - YACAMAN, MJ; TORRES, VG (UNAM, Instit de Fisic, centro de Inves Materiales, 1978)
The microscopic morphology of evaporated (100) surfaces of NaCl crystals has been studied by means of gold decoration, replication, and electron microscopy. Closely spaced monoatomic steps were observed following a 15 min evaporation in air at 580 degrees
J ECON ENTOMOL
Keywords: GOLD DECORATION, MONOATOMIC, STEPS, SURFACE, NACL, CRYSTALS, PRODUCED DURING, EVAPORATION, AIR; FISICA; QUIMICA FISICA; CRISTALES LIQUIDOS